Pengaruh Pengendalian Internal, Kesesuaian Kompensasi, Dan Moralitas Individu Terhadap Kecenderungan Kecurangan Akuntansi - Novrita Aulia Rahmi; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to prove empirically about: the influence of internal control, compensation compatibility and individual morality on accounting fraud tendency. Data for this study was obtained from samples of 26 SKPD Solok Regency. Collecting data in this study are primary data obtained from questionnaires distributed directly to the respondents. Total respondents which is used in this research are 78 respondents (100%). The analyzing method used in this research is Double Regression methods using SPSS (Statistical Product and Service Solution) version 24. Result of the study indicates that internal control negative influence to accounting fraud tendency. Compensation compatibility and individual morality positive influence to accounting fraud tendency. The coefficient of determination in this study was 76,6%, while 23,4% is influenced by other variables.